An evaluation of biosynthesized nanoparticles in biodiesel as an enhancement of a VCR diesel engine. (15th November 2022) - Anish, M.; Bency, P.; Jayaprabakar, Jayaraman; Joy, Nivin; Jayaprakash, V.; Sahaya Susmi, S.K.; Aravind Kumar, J.; Ansar, Sabah; Rezania, Shahabaldin
Highlights: Homogeneous solution is made by mixing nanoparticles such as titanium oxide (TiO2 ) and zinc oxide (ZnO). Enhanced mixing and improved reactivity of such nanoparticles. Higher surface area to volume ratio is observed. Improved engine's performance and higher efficiency is resulted. Abstract: Using three different fuel sequences –biodiesel–diesel (B20), biodiesel–chemically and biologically synthesized nanoparticles(B20A30C30), and biodiesel–chemically and biologically synthesized nanoparticles (B20A30C30). This study investigates a single-cylinder variable compression ratio diesel engine's combustion, efficiency, and emission characteristics (B100A30C30). The ultrasonicator is employed in concert with 30 parts per million (ppm) concentration of titanium oxide (TiO2 ) and zinc oxide (ZnO), two typical nanoparticles found in fuel mixtures, to form a homogenous solution. As a result of the greater mixing and chemical reactivity offered by nanoparticles' higher surface area to volume ratio during combustion, diesel engines' combustion, performance, and emission characteristics have all been improved. The engine with nanoparticles (B20A30C30) has a 16% higher brake thermal efficiency than the engine with conventional particles (B100). Following that, nitrogen oxide emissions were reduced by 32%, carbon monoxide emissions were reduced by 62%, hydrocarbon emissions were reduced by 48%, and smoke emissions were reduced by 40%.